2016
DOI: 10.1002/pon.4114
|View full text |Cite
|
Sign up to set email alerts
|

Savoring moderates the association between cancer‐specific physical symptoms and depressive symptoms

Abstract: The findings suggest that savoring is positively associated with physical and psychological functioning among people with cancer. The link between physical symptoms and depressive symptoms could be exacerbated at lower levels of savoring. Fostering savoring beliefs and practices could be a significant psychological component of symptom management among cancer patients. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…Especially relevant to the present study, Hou et al () demonstrated savouring to be associated with physical symptoms, psychological distress, and psychological well‐being among recently diagnosed cancer patients. Additionally, savouring was found to moderate the relationship between cancer specific physical and depressive symptoms.…”
Section: Introductionmentioning
confidence: 59%
“…Especially relevant to the present study, Hou et al () demonstrated savouring to be associated with physical symptoms, psychological distress, and psychological well‐being among recently diagnosed cancer patients. Additionally, savouring was found to moderate the relationship between cancer specific physical and depressive symptoms.…”
Section: Introductionmentioning
confidence: 59%
“…The current study adds to the existing body of knowledge by exhibiting the positive psychological pathways of perceived capability of savouring the moment in life adversities. Recent studies have identified the benefit of perceived capability of savouring the moment in adaptation to cancer, but the studies focused on distress including physical symptoms, anxiety and depressive symptoms, or caregiving burden (Hou et al, ). Perceived capability of savouring the moment might be a reactive process of attending to and being fully engaged in positive experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Note: standardized maximum likelihood coefficients in the APIM model. *p < 0.05, **p < 0.01, ***p < 0.001 burden (Hou et al, 2016(Hou et al, , 2017. Perceived capability of savouring the moment might be a reactive process of attending to and being fully engaged in positive experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding the above limitations, this study together with some recent ones (Hou et al, 2016(Hou et al, , 2017 point to feasible directions for dyadic psychosocial education among cancer patients and caregivers. They could be instructed on skills of seeking, providing and acknowledging timely support for each other with reference to differential exposure to cancer stress (Northouse, Katapodi, Song, Zhang, & Mood, 2010).…”
Section: Study Limitationsmentioning
confidence: 81%